Penggunaan Teknologi Branchless Banking Sebagai Alat Memperluas Inklusi Keuangan Masyarakat Kab. Kampar – Riau - Fitri Ayu Nofirda; Dwi Dewisri Kinasih (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2021)
This study aims to see the effect of branchless banking on financial inclusion. The sample in this study amounted to 96 respondents. The sampling technique used was purposive sampling method. Data collection techniques using primary data in the form of questionnaires and secondary data. This study uses a regression test to test the hypothesis. This study found that branchless banking has a positive effect on the financial inclusion of the people of Kampar Regency, Riau.